Pattern Of Distribution Of Congenital Anomalies In Stillborn: A Hospital Based Prospective Study - SUNETHRI PADMA; RAMAKRISHNA D; JIJIYA BAI P; RAMANA PV (International Journal of Pharma and Bio Sciences, 2011)
Background: Congenital anomalies (CAs) are one of the most common causes of disability in developed and developing countries. Aims: To determine frequency, pattern of distribution of CAs in still born with a focus on sex ratio. Methods: Maternal history, associated risk factors, socio economic status, sex and type of CAs in babies were recorded. Diagnosis of CAs was based on findings of autopsies conducted. Results: Autopsy was conducted on 102 still born babies, of which 28 were found to have CAs. The occurrence of CAs was more in males than females. The pattern CAs included CNS, Digestive system, urinary system and circulatory system. In CNS group, Anencephaly was the most common malformation followed by Spinabifida. Conclusion: Frequency of CAs were more common in males than females, with CNS anomalies being the most common and also these anomalies were more common in gestational age of 29-32 weeks.